2005
DOI: 10.1177/039139880502800212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valsartan versus Lisinopril on Peritoneal Sclerosis in Rats

Abstract: Background Peritoneal sclerosis (PS) is one of the most serious causes of failure in long-term peritoneal dialysis. Angiotensin II is known to promote fibrosis and inflammation in various tissues. We previously showed that ACE inhibitors (ACEIs) have beneficial effects on hypertonic PD solutions (3.86% PD) induced peritoneal alterations. The aim of this study is to compare the effects of an ACEI and a receptor blocker on peritoneal alterations induced by hypertonic PD solutions in rats. Methods Forty-three non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
2
39
0
2
Order By: Relevance
“…18,41 A number of medications, including valsartan, lisinopril, enalapril, octreotide, dipyramidole, and pentoxyphyline, were used to preserve longevity of PD yielding some degree of success. [9][10][11]37,48 There is only one report concerning the effects of atorvastatin. 49 In this study, atorvastatin was chosen to test its effects on the development of peritoneal fibrosis and to consider possible pathogenetic mechanisms using the aforementioned experimental model, 48 because of antioxidant, anti-inflammatory, [50][51][52] antiproliferative, atherosclerotic plaque stabilizing, anticoagulant, and renoprotective [53][54][55] effects of statins, independent of their lipid-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,41 A number of medications, including valsartan, lisinopril, enalapril, octreotide, dipyramidole, and pentoxyphyline, were used to preserve longevity of PD yielding some degree of success. [9][10][11]37,48 There is only one report concerning the effects of atorvastatin. 49 In this study, atorvastatin was chosen to test its effects on the development of peritoneal fibrosis and to consider possible pathogenetic mechanisms using the aforementioned experimental model, 48 because of antioxidant, anti-inflammatory, [50][51][52] antiproliferative, atherosclerotic plaque stabilizing, anticoagulant, and renoprotective [53][54][55] effects of statins, independent of their lipid-lowering effects.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] To eliminate the deleterious effects of long-term PD on peritoneal function and structure, many agents including valsartan, lisinopril, enalapril, and octreotide were tried yielding some beneficial outcomes. [9][10][11] Statins are generally prescribed to treat hyperlipidemia; however, data concerning anti-inflammatory, antiproliferative, and antioxidant effects of statins are accumulating. [12][13][14][15][16] In this study, we aimed to test the effects of atorvastatin on peritoneal functions and peritoneal histology in rats on PD in terms of the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This is only an indirect indication for the widespread use of these new solutions as a means to prevent EPS, but it seems more promising than a misunderstood precautionary principle. The inhibition of renin-angiotensin system should also be considered as the elective therapy of hypertension in PD patients since a number of papers [37][38][39] clearly indicate a role of ACE-inhibition in preventing peritoneal fibrosis.…”
Section: Exploring Ways To Prevent Epsmentioning
confidence: 99%
“…It is reported that the peritoneal membrane damage is however prevented by angiotensin convertingenzyme inhibitors and angiotensin II receptor blockers [9][10][11]. There is improvement in prognosis of kidney injury patients using mineralocorticoid receptor antagonist [12,13].…”
Section: Introductionmentioning
confidence: 99%